2005
DOI: 10.1175/jtech-1657.1
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Quality Assurance Procedures for an Applied Climate Information System

Abstract: Valid data are required to make climate assessments and to make climate-related decisions. The objective of this paper is threefold: to introduce an explicit treatment of Type I and Type II errors in evaluating the performance of quality assurance procedures, to illustrate a quality control approach that allows tailoring to regions and subregions, and to introduce a new spatial regression test. Threshold testing, step change, persistence, and spatial regression were included in a test of three decades of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 10 publications
1
73
0
1
Order By: Relevance
“…2, 3 and 4. The results obtained in this work are similar to the results of Hubbard et al (2005). The results for the threshold analysis indicate that approximately 2 % of the data would be flagged for maximum, minimum and mean temperature if an f value of 2.3 is used.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…2, 3 and 4. The results obtained in this work are similar to the results of Hubbard et al (2005). The results for the threshold analysis indicate that approximately 2 % of the data would be flagged for maximum, minimum and mean temperature if an f value of 2.3 is used.…”
Section: Resultssupporting
confidence: 84%
“…1), using data only from a single site. Three procedures were tuned to the prevailing climate: seasonal thresholds, seasonal rate of change and seasonal persistence (Hubbard et al, 2005). These tests are related to station climatology at the monthly level, using dynamic limits for each variable.…”
Section: Source Of Datamentioning
confidence: 99%
“…On the basis of these principles, the number of spatial neighbors n is set to 10. Hubbard et al [20,21] suggested that the number of temporal neighbors can be set to about half of the research period. In this study, the research period is 26, therefore the number of temporal neighbors m is also set to 10.…”
Section: Experiments and Results Analysismentioning
confidence: 99%
“…Therefore, GWR and STGWR are unsuitable for estimating missing data. A spatial regression test (SRT) estimates the missing data in the station of interest by using the neighboring stations [20,21]. For each neighboring station, a regression estimate (x i = a i + b i y i ) is calculated.…”
Section: Related Workmentioning
confidence: 99%
“…This helps explain that normals estimated from inverse distance weighting or arithmetically averaging were not as accurate as IWSTD, which assigns more weights on the neighboring stations with temperatures closer to the temperature of the target station. IWSTD is also better than other schemes we tested, including the Spatial Regression Test (Hubbard et al, 2004), an interpolation scheme newly developed for quality assurance purposes.…”
Section: Spatial Interpolation Schemementioning
confidence: 86%